NLRP3 Inflammasome-Mediated Osteoarthritis: The Role of Epigenetics - Yuzhou Liu; Ying Wang; Ping Yan; Ning Cui; Kejin Xu; Da Liu; Yuan Tian; Lingling Cao (Biology, 2025)
The prevalence of osteoarthritis (OA) notably surges with age and weight gain. The most common clinical therapeutic drugs are painkillers, yet they cannot impede the deteriorating course of OA. Thus, understanding OA’s pathogenesis and devising effective therapies is crucial. It is generally recognized that inflammation, pyroptosis, and OA progression are tightly linked. The activation of NLRP3 inflammasome can lead to the discharge of the pro-inflammatory cytokines Interleukin-1β and IL-18, intensifying subsequent inflammatory reactions and promoting OA development. Conversely, the imbalance caused by deacetylase-regulated NLRP3 inflammasome underlies the chronic mild inflammation related to degenerative diseases. Therefore, this article expounds on the mechanism of OA pathogenesis and the role of histone deacetylases (HDACs) in NLRP3 inflammasome-triggered OA, and illustrates the application of HDAC inhibitors in OA, striving to provide more insights into novel OA treatment approaches.